The single leg triple hop for distance test - Williams, M.; Squillante, A. D.; Dawes, J. (Strength and Conditioning Journal, 2017)
The single leg triple hop for distance test is an easy and inexpensive method of assessing a player's injury risk. This article provides a detailed description of how to perform and analyze the results of this test.